The future of the 21st century education inspectorate: challenges and opportunities - Galicia Mangas, Francisco Javier (Avances en Supervisión Educativa, 2024)
This article seeks to address a long-standing issue: How should the Inspectorate be able to address the challenges posed by education in the 21st century? Every challenge faced by the Inspectorate is an opportunity for improvement, but it opens a path that cannot be travelled without taking risks. Precisely, in order to help them along this complex path, on the basis of a description of the current framework in which the Inspectorate carries out its work and the situation of education, different alternatives and proposals are formulated, in relation to the professional and personal skills and competencies necessary for the adequate performance of this work, with the internal organisation model, both traditional and more innovative functions carried out, and the system of access and training of education inspectors in our country, and in other comparable models.